THE (S) DESIGN (S) LANGUAGE GUIDING (M) DISCURSIVE PRACTICES IN PORTUGUESE LANGUAGE CLASSES OF SECONDARY EDUCATION - Reboucas, Jose Valter; Macedo Costa, Mikaeli Cristina; Pontes, Antonio Luciano [UNESP] (Univ Estado Rio Grande Norte, 2015)
This study aimed to analyze what kind of conception of language guides the discursive practices in Portuguese classes of high school and how this influences the reader proficiency of students. In addition, we sought to examine whether these proposals include the inclusion of the diversity of genres as very important elements for the socio-cognitive interaction of students in physical and virtual environments. Therefore, methodologically, was guided from the teaching practice, noting issues such as: What reading way is crafted in discursive practice in the classroom? The discursive proposal covers the diversity of genres? In analyzing the results, it was discussed about the contributions this research brought to the author, suggesting that further studies be conducted in order thus to an educational training based on literacy principles.
Keywords: Conceptions of language; Discursive practices; Literacy